BARRIERS TO DRUG PLANNING IN THE PHARMACY UNIT OF HOSPITAL X IN MALANG, EAST JAVA, INDONESIA: MANAGERIAL AND OPERATIONAL PERSPECTIVES - Zuhroh, Fifi Kurnaini; Ahsan, Ahsan; Khulud, Khoiron (Universitas Brawijaya, 2025)
Drug planning, a key responsibility of the hospital’s pharmacy unit, plays a crucial role in ensuring that drug management is safe, effective, and efficient. Inadequate drug planning can lead to stockouts and dead stock which negatively affect the quality of patient care and resource utilization. The purpose of this study was to identify the obstacles hindering the optimal implementation of the drug planning process in the pharmacy. This study employed a qualitative approach in the form of a case study. Data collection was carried out from September to October 2024 through in-depth interviews with informants and direct observation through document review. Informants were selected using purposive sampling and included the Assistant Manager of Medical Support, the Head of the Pharmacy Unit, and the Person in Charge of the Pharmacy Warehouse. The data analysis was conducted using triangulation to check the validity of the data. The results of the study revealed that there were five main problems that caused obstacles in planning so pharmaceutical management was not optimal. These obstacles are the imbalance between the workload and the number of officers, lack of officer skills, the absence of a drug planning team, inappropriate drug planning calculation and methods, and inadequate hospital information system (HIS) related to drug planning. In conclusion, although the management of drug planning and procurement in the pharmacy unit of Hospital X, Malang City, East Java, Indonesia, has been carried out, its implementation remains suboptimal because of various managerial and operational barriers.